Accessory nuclei in the oocytes of pachycondyla (Neoponera) villosa (Hymenoptera: Ponerinae) as a source of annulate lamellae - Mathias, Maria Izabel Camargo [UNESP]; Caetano, Flávio Henrique [UNESP]; Denardi, Sandra Eloisi [UNESP] (My University, 2010)
In insects' oocytes, structures called accessory nuclei can be observed. They are similar to the nucleus of the oocyte and have been detected in Hymenoptera as well as in other groups, with their source and functions still under discussion (Cassidy Sc King 1972). Through the use of histochemical techniques as well as ultrastructural ones, it was possible to observe several accessory nuclei surrounding the oocyte nucleus in the immature oocytes of Pachycondyla (Neoponera) villosa ants. Morphologically they were seen to be round and smaller than the germinal vesicle. When using these histochemical techniques, the only positive reaction was for proteins. Ultrastructurally they have the same morphology as the oocyte nucleus and a fine and electrondense granulation was observed inside them. The function of accessory nuclei in P {Neoponera) villosa is probably as a source of anullate lamellae and as an RNA reservoir in the oocytes. In mature oocytes (stage III), these structures are not observed, suggesting that they disappeared before this stage by releasing their contents into the oocytes' cytoplasm, according to Camargo-Mathias and Caetano (1993).
Keywords: Accessory nuclei; Annulate lamellae; Ants; P. (neoponera) villosa